PEMBERIAN SENAM JANTUNG SEHAT BAGI KEBUGARAN JASMANI LANSIA PADA IBU IBU AISYIYAH KAJEN - Robby Henriana, Robby Henriana (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2023)
The purpose of this community service is to improve the physical fitness of Aisyiyah's mother by providing an increase in physical exercise activity during the covid 19 pandemic. In increasing knowledge about physical activity in sports during the covid pandemic, activities are carried out with Health protocols. This activity is done by doing healthy heart exercises. The results of the implementation of this community service activity are expected to provide insight into what are the benefits and how to maintain physical fitness to stay fit and not experience fatigue..